Analisis Harga Pokok Produksi dan Break Even Point Pada UD Niki Mawon - Revlin Lambang; Daniel Nemba Dambe (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2023)
The purpose of this study was to determine the cost of producing tempe, the break-even point, and the margin of safety for tempe production at UD Niki Mawon. The data collection technique used in this research is interview. The data analysis instrument used in this research is using the full costing method for calculating the cost of production, using the break-even point calculation method in units and in rupiah, and using the method of comparing planned sales with breakeven sales to obtain a margin of safety. The results of the research on the cost of production for small tempe products amounted to IDR 800,127,888 or IDR 882 per unit, boxed tempe was IDR 2,068,420,022 IDR 1,131 per unit, and large tempe was IDR 126,687,739 or Rp. 2,908 per unit. UD Niki Mawon will reach a break-even point if it sells 625,063 units of small tempe products or IDR 624,177,419, 702,243 units of boxed tempeh or IDR 1,054,178,223, and 7,385 large tempe products or IDR 29,544,357. UD Niki Mawon has a safety limit for small tempeh of 45%, boxed tempeh of 60%, and 90% of large tempeh.